The Application of Booklet for Providing Mental and Psychosocial Support (MHPSS) to Elderly during COVID-19 Pandemic - Nurmawati, Thatit; Wulandari, Nawang; Rahmawati, Anita; Aziz, Aurizal Ahmad; Febriana, Lutvi; Permatasari, Intan; Parwati, Ida (STIKes Patria Husada Blitar, 2021)
The condition of the COVID-19 Pandemic which is full of uncertainty makes the elderly easily plagued by feelings of excessive anxiety which has an impact on physical health conditions. The purpose of the community service was to provide mental and psychosocial support (MHPSS) during Covid-19 pandemic through booklets. The method used health education by distributing booklets. The activity was conducted in Blitar district area through the online network on February 2021 with 21 elderly people as the respondents. The results showed that the elderly were able to follow all the activities given and able to re-practice physical activities that could be done to deal with anxiety as a psychological impact of COVID-19 properly. Batik activity is one form of occupational therapy for People with mental disorders to continue to be carried out so that independence and entrepreneurial spirit can increase, so they will be more productive. The Mental and Psychosocial Support (MHPSS) for all elderly groups in the community needs to be continuously carried out by involving elderly cadres as an effort to control anxiety as a result of the COVID-19 Pandemic